1959
DOI: 10.6028/nbs.mono.5
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of documents by lamination

Abstract: The functions of the National Bureau of Standards are set forth in the Act of Congress, March 3, 1901, as amended by Congress in Public Law 619, 1950. These include the development and maintenance of the national standards of measurement and the provision of means and methods for making measurements consistent with these standards; the determination of physical constants and properties of materials; the development of methods and instruments for testing materials, devices, ana structures; advisory services to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1961
1961
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The solvent plasticizer used to plasticize the cel A5a is bis(2-methoxyethyl) phthalate. Wilson and Forshee concluded in their research that the degradation of CA was principally oxidative in nature and moisture did not considerably affect the degradation [22]. They also observed that TPP can act like a stabilizer; ether esters plasticizers, like ethoxy ethyl phthalate, bis(2-(2-ethoxyethoxy)ethyl) phthalate, and also bis(2-methoxyethyl) phthalate (DMEP), can cause serious degradation.…”
Section: Peak # Retention Time (Min)mentioning
confidence: 99%
See 1 more Smart Citation
“…The solvent plasticizer used to plasticize the cel A5a is bis(2-methoxyethyl) phthalate. Wilson and Forshee concluded in their research that the degradation of CA was principally oxidative in nature and moisture did not considerably affect the degradation [22]. They also observed that TPP can act like a stabilizer; ether esters plasticizers, like ethoxy ethyl phthalate, bis(2-(2-ethoxyethoxy)ethyl) phthalate, and also bis(2-methoxyethyl) phthalate (DMEP), can cause serious degradation.…”
Section: Peak # Retention Time (Min)mentioning
confidence: 99%
“…Cel A5a is plasticized with bis(2-methoxyethyl) phthalate (DMEP) and TPP; both plasticizers are suspected to cause degradation of the cellulose acetate polymer [21,22]. DMEP is a solvent plasticizer; if added in a large amount, it will solve the cellulose acetate.…”
Section: Peak # Retention Time (Min)mentioning
confidence: 99%
“…Silking has been used, with variations, in this country and in Europe until recent times. However, it began to fall into disfavor in many sectors in the 1930s as the research efforts of the National Bureau of Standards and of William J. Barrow publicized the qualities of cellulose acetate as the preferred material for the lamination of documents (10,11). Equip ment for cellulose acetate/tissue lamination according to the Barrow system was installed in the Library of Congress Branch of the G.P.O.…”
Section: Unbound Materialsmentioning
confidence: 99%
“…Similar institutions exist around the world with similar goals. Some studies related to the protection of historical documents refer to the use of acetate films [3]. These chemically stable films are wrapped around documents to protect them.…”
Section: Introductionmentioning
confidence: 99%